Queer N/Oceans: Vore and Child Abuse in Ananda Devi’s La vie de Joséphin le fou - Ireland, Benjamin Hiramatsu (Dalhousie French Studies)

(untitled) (Department of French, Dalhousie University, 2022)
This article argues that in Ananda Devi’s La vie de Joséphin le fou (2003), the protagonist Joséphin assumes the form of a human-eel monster, engaging in acts of vorarephilia or “vore,” to satiate a murderous desire underwater. This analysis conceives Joséphin’s aquatic world as a paradoxically queer, abject, and maternal space in which Joséphin terrorizes two underage children as both their abductor and protector. Devi further reconfigures in her novel the archetype of the protective eel in Mauritian shamanistic practices by depicting Joséphin as a predatorial human-eel figure. Joséphin’s violence against the children as he assumes such a monstrous embodiment serves as a metaphor for child sexual abuse in Mauritius where, at the time of the novel’s publication, an estimated 2,600 children were victims of molestation.